Analysing interlinkages of Indian stock market with other emerging Asian markets. (15th June 2021) - Goel, Himanshu; Singh, Narinder Pal
This study aims to analyse the international linkage of Bombay Stock Exchange (BSE) Sensex with the fastest emerging markets namely China, Korea, and Taiwan. The results of the Johansen cointegration test reveal that there exist no significant cointegration among the selected markets. Granger causality test reveals unidirectional causality running from India to China and bidirectional causality between India and Korea. However, no significant short run causality was found between India and Taiwan. The results of forecasted error variance decomposition (FEVD) and impulse response function (IRF) reveal that the Indian and Chinese stock markets are majorly impacted by their own shocks whereas the stock markets of Korea and Taiwan are significantly affected by shocks in BSE as well. The results of this study may prove significant for retail investors, portfolio managers, foreign institutional investors and high networth individuals in designing the optimal portfolio.